Approaches to characterizing human health risks of exposure to fibers. - Vu, V T (1997)
Naturally occurring and man-made (synthetic) fibers of respirable sizes are substances that have been identified by the U.S. Environmental Protection Agency (U.S. EPA) as priority substances for risk reduction and pollution prevention under the Toxic Substances Control Act (TSCA). The health concern for respirable fibers is based on the link of occupational asbestos exposure and environmental erionite fiber exposure to the development of chronic respiratory diseases, including interstitial lung fibrosis, lung cancer, and mesothelioma in humans. There is also considerable laboratory evidence indicating that a variety of fibers of varying physical and chemical characteristics can elicit fibrogenic and carcinogenic effects in animals under certain exposure conditions. This paper discusses key scientific issues and major default assumptions and uncertainties pertaining to the risk assessment of inhaled fibers. This is followed by a description of the types of assessment performed by the U.S. EPA to support risk management actions of new fibers and existing fibers under TSCA. The scope and depth of these risk assessments, however, vary greatly depending on whether the substance under review is an existing or a new fiber, the purpose of the assessment, the availability of data, time, and resources, and the intended nature of regulatory action. In general, these risk assessments are of considerable uncertainty because health hazard and human exposure information is often incomplete for most fibers. Furthermore, how fibers cause diseases and what specific determinants are critical to fiber-induced toxicity and carcinogenicity are still not completely understood. Further research to improve our knowledge base in fiber toxicology and additional toxicity and exposure data gathering are needed to more accurately characterize the health risks of inhaled fibers.